Gastroprotective properties of flavonoid-rich extract of Pulicaria odora against ethanol-induced gastric ulcer in mice - Khadidja Boudebbaz; Manel Brouk; Roumaissa Laalem; Nada Zabaiou (Heliyon)
Pulicaria odora has been traditionally used in northeastern Algeria for treating gastrointestinal disorders, particularly ulcers. This study aimed to assess the gastroprotective, anti-inflammatory, and antioxidant properties of a crude hydroalcoholic extract derived from the leaves of Pulicaria odora, as well as its subsequent fractions. The gastroprotective effect was studied in an ethanol-induced ulcer model in mice. The in vitro antioxidant activity was quantified via the DPPH, and ABTS methods. In vitro anti-inflammatory activity was investigated through the human red blood cell membrane stabilization method and the bovine serum albumin denaturation method. The in vivo anti-inflammatory properties of the crude extract were assessed in mice via a carrageenan-induced acute paw edema model. The crude extract significantly inhibited gastric ulcer formation in a dose-dependent manner, achieving a reduction of up to 99.91 % at a dose of 200 mg/kg. Among the fractions, the aqueous fraction exhibited the most potent gastroprotective effect, with a notable dose-dependent response and high ulcer inhibition rates (95.56 % at 50 mg/kg). Additionally, the crude extract displayed strong in vitro and in vivo anti-inflammatory activity and a high free radical scavenging capacity; with IC50 values comparable to those of ascorbic acid. LC-ESI-MSn analysis led to the identification of nine flavonoid derivatives, which were subsequently subjected to molecular docking techniques to predict their antiulcer activity. These results suggest that both glycosylated and aglycone flavonoids derived from P. odora have the potential to inhibit gastric acid secretion by targeting the proton pump.